Konsep Qana’ah Dalam Keluarga Di Era Digital Perspektif Al-Qur’an - Umam, Khotibul; Munana, Nila (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
In the fast-paced digital era filled with information flows and a consumerist lifestyle, contentment (qana'ah) is an important value that must be continuously observed and instilled. The purpose of qana'ah is to foster gratitude, create inner peace, and maintain balance in life. This study aims to examine the concept of qana'ah and its relevance in today's digital era. The type of research used is library research, with qualitative descriptive analysis techniques, by collecting data and materials related to the discussion theme and its problems, obtained from library sources. Furthermore, it was analyzed using the thematic interpretation method. The results of the study on the explanation of the Qur'an on the concept of qana'ah are an attitude of contentment with the distribution of sustenance from Allah, feeling sufficient with what one has, not being greedy for the sustenance of others, being grateful for even the smallest blessings. The relevance of the concept of qana'ah to the lifestyle of digital society is by choosing a Simple Living lifestyle, Enough Is Enough, Contentment Lifestyle, Gratitude Living and Live With Less. Amidst the onslaught of a hedonistic lifestyle, contentment teaches us to maintain peace of mind, avoid the stress of a competitive lifestyle, and foster an awareness that true happiness is not measured by material things but by inner satisfaction and faith